Employee attraction and retention: The case of nursing in Western Australia - Naude, Marita; Jefferson, Therese (John Curtin Institute of Public Policy, Curtin University of Technology, 2009)
Western Australia’s population is both growing and ageing rapidly. This has significant implications for the State’s health sector, including its capacity to plan for and manage an appropriately skilled workforce. This study reports on employee attraction and retention in three hospitals that have been relatively successful in managing labour attraction and turnover. The study focuses on employees’ perspectives about the key factors which encouraged them to seek and remain in employment with their current hospital. The key conclusion is that the factors which first attracted employees to their current employer provide some contrasts with the factors that facilitate their retention. This has important implications for successfully integrating human resource practice into public health policies in a context of increasing demand for health services. Although this study was conducted in the health services, some of the insights and understandings are useful to other sectors and organisations.